Pyknotic chromatin in mitonucleons elevating in syncytia undergo karyorhhexis and karyolysis before coalescing into an irregular chromatin mass: Differentiation of Ishikawa Domes, Part 2 - Fleming, Honoree (PeerJ PrePrints, 2016)
Pyknosis, karyorrhexis and karyolysis, harbingers of programmed cell death in many systems, appear to be driving forces that transform Ishikawa monolayer epithelial cells into differentiated dome cells. The heterochromatin affected by these process is contained in multiple nuclei aggregated in the syncytia that form when Ishikawa monolayers are stimulated to differentiate (Fleming, 2016a). The nuclear aggregates are enveloped in a double membrane staining for the endogenous biotin in mitochondrial carboxylases. The structure called a mitonucleon becomes vacuolated, along with the heterochromatin it envelops, and this structure elevates with the apical membrane of the syncytium 6 to 8 hours into the 20 hour differentiation, becoming increasingly pyknotic. This phase of the differentiation comes to an end when the mitonucleon membranes are breached and nuclei emerging from the aggregated state can be seen to fragment explosively. Fragmented DNA associates with an array of microtubules, filling the large central clearing of the predome. Some chromatin remains unfragmented and can be seen of the edges of the predome clearing. Cell death does not occur. Instead, the fragmented DNA coalesces into an irregular mass within the apical and basal membranes of the predome under which fluid has been accumulating. From the chromatin sheet, nuclei emerge amitotically as described in Part 3 of this series (Fleming, 2016c).
Keywords: karyorhhexis; karyolysis; amitosis; chromatin deconstruction; microtubules; quasi-parallel chromatin fiber array; apical membrane protrusions; differentiation looking like apoptosis